HALAL TOURISM: BIBLIOMETRICS APPROACH - Destrianti Karmanto, Gina; Fakhri Al-Kahfi, Muhammad; Sari Kasmiarno, Kurnia (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to analyze research trends on halal tourism using a bibliometric approach. Halal tourism is a growing segment of the tourism industry, driven by the increasing Muslim population and the demand for services that comply with sharia principles. Using the Scopus database, this study collected and analyzed 375 articles published in the period 2015–2025. The analysis was carried out using the bibliometric method using VOSviewer software to identify publication trends, dominant keywords, author collaboration networks, and research distribution by country and field of study. The results showed that publications on halal tourism have increased significantly, especially in the aspects of sustainability and digitalization of halal tourism services. This study found that Indonesia and Malaysia are the countries with the highest number of publications. Key words: Halal Tourism; Bibliometrics; Publication Trends; Scopus; VOSviewer